Developing Learning Media for Inclusive Education: A Collaborative Community Project in Rahuning Asahan - Murniati Br Barus; Gumarpi Rahis Pasaribu (EPISTEMOLOGI : JURNAL PENGABDIAN MASYARAKAT DAN PENELITIAN, 2025)
Inclusive education remains a significant challenge in rural areas where access to appropriate learning media and professional training is limited. This study aimed to develop contextually relevant and accessible learning media for students with special needs through a collaborative, community-based approach in Rahuning, Asahan. Utilizing a qualitative descriptive method and grounded in participatory action research (PAR), the project engaged elementary school teachers, parents, local education officers, and university lecturers in co-designing and implementing inclusive learning tools. Data were collected through interviews, focus group discussions, classroom observations, and document analysis. The results demonstrated that active stakeholder involvement led to the creation of practical, low-cost, and engaging learning materials tailored to various disabilities. Furthermore, the process fostered increased awareness, empathy, and a sense of ownership among participants, leading to a shift toward more inclusive practices in the classroom. The study concludes that inclusive education can be significantly improved in under-resourced settings when driven by community collaboration and local empowerment. This research contributes a practical model for inclusive media development that is both sustainable and scalable in similar educational contexts.